2018
DOI: 10.1103/physrevd.98.104047
|View full text |Cite
|
Sign up to set email alerts
|

Axial quasinormal modes of neutron stars in R2 gravity

Abstract: The spectrum of frequencies and characteristic times that compose the ringdown phase of gravitational waves emitted by neutron stars carry information about the matter content (the equation of state) and the underlying theory of gravity. Typically, modified theories of gravity introduce additional degrees of freedom/fields, such as scalars, which result in new families of modes composing the ringdown spectrum. One simple but physically promising candidate is R 2 gravity, which effectively introduces an additio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 82 publications
3
49
0
Order By: Relevance
“…Alternatively, in [14], was shown that the Ellis wormhole also can be understood as an electrovacuum solution of EsGB gravity with a material source consisting of a source-free electric field and a real scalar field. The Ellis WH have been extensively studied, and its properties like gravitational lensing [15], quasi-normal modes [16], stability [17] and shadows [18], have been thoroughly investigated. In this case the metric (16) reduces to…”
Section: Vmentioning
confidence: 99%
“…Alternatively, in [14], was shown that the Ellis wormhole also can be understood as an electrovacuum solution of EsGB gravity with a material source consisting of a source-free electric field and a real scalar field. The Ellis WH have been extensively studied, and its properties like gravitational lensing [15], quasi-normal modes [16], stability [17] and shadows [18], have been thoroughly investigated. In this case the metric (16) reduces to…”
Section: Vmentioning
confidence: 99%
“…Note that in the above equations (29)-(31) we have fixed the "spirality" to +1, the only case discussed in this work. Nonetheless, all the qualitative properties of the Dirac stars that we present in the next Section are not affected by this choice (for instance, other properties of the Dirac field on static and spherically symmetric configurations, such as the quasinormal modes, are not qualitatively affected by the change of spirality [15]).…”
Section: S = 1/2: Massive Dirac Fieldsmentioning
confidence: 99%
“…These angular solutions are the spinor monopole harmonics for a (D − 2)-sphere[14]; also, they are related with the solutions of the angular part in[15].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In these papers, an efficient method to calculate the QNM spectra was presented. This method was also applied to study QNMs in alternative theories ( [16], [17], [18], [19], [20]). Here we will present an enhancement of the method that will allow us to calculate the w-QNM spectra of thousands of EOSs in a reasonable time.…”
Section: Introductionmentioning
confidence: 99%